Trajectory of an object sliding across an incline. (1st September 2022) - Cross, Rod
Abstract: Measurements and calculations are presented showing how the trajectory of an object sliding across an inclined plane varies with the launch and incline angles. The trajectory depends on the magnitude and direction of the sliding friction force. The experiment is easy to set up, can be analysed using a video camera, and would be suitable for a student experiment or demonstration.